2014
DOI: 10.1074/jbc.m114.592360
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200 Is Induced by Thioredoxin-interacting Protein and Regulates Zeb1 Protein Signaling and Beta Cell Apoptosis

Abstract: Background: Beta cell apoptosis is a key factor in diabetes, but the mechanisms are not well understood. Results: Beta cell miR-200 is induced by thioredoxin-interacting protein (TXNIP) and diabetes, directly targets Zeb1, up-regulates E-cadherin, and promotes apoptosis. Conclusion: This novel TXNIP/miR-200/Zeb1/E-cadherin signaling pathway links miR-200 to beta cell apoptosis, control of epithelial-mesenchymal transition, and diabetes. Significance: The results provide new insight into microRNA biology and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 39 publications
1
75
0
Order By: Relevance
“…The induction of miR-204 triggered by TXNIP was found to reduce MafA expression and to cause an impairment in insulin biosynthesis [48]. In contrast, miR-200 overexpression promotes β-cell apoptosis and inhibits epithelial-mesenchymal transition, a process thought to be involved in compensatory β-cell mass expansion [47].…”
Section: Contribution Of Other Mirnas To Compensatory β-Cell Mass Expmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of miR-204 triggered by TXNIP was found to reduce MafA expression and to cause an impairment in insulin biosynthesis [48]. In contrast, miR-200 overexpression promotes β-cell apoptosis and inhibits epithelial-mesenchymal transition, a process thought to be involved in compensatory β-cell mass expansion [47].…”
Section: Contribution Of Other Mirnas To Compensatory β-Cell Mass Expmentioning
confidence: 99%
“…However, transgenic mice overexpressing miR-802 developed glucose intolerance and insulin resistance, suggesting the involvement of this miRNA in the regulation of glucose homeostasis in vivo [45]. Another group of miRNAs, including miR-204 and miR-200 family members, has been shown to be induced by the Thioredoxin-interacting protein (TXNIP), a cellular redox regulator that is up-regulated in diabetes and triggers β-cell apoptosis [47,48]. The induction of miR-204 triggered by TXNIP was found to reduce MafA expression and to cause an impairment in insulin biosynthesis [48].…”
Section: Contribution Of Other Mirnas To Compensatory β-Cell Mass Expmentioning
confidence: 99%
“…The proapoptotic and diabetogenic functions of Txnip are associated with the Txnip-mediated changes in miRNAs, such as miR-204 and miR-200. 102,103 Txnip can induce miR-204 expression, which in turn regulates Mafa expression and thus modulates β-cell functions, such as insulin production. 102 In addition, Txnip impairs β-cell functions by inducing miR-200.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%
“…102 In addition, Txnip impairs β-cell functions by inducing miR-200. 103 miR-200 has been demonstrated to target and decrease Zeb1 and promote β-cell apoptosis. 103 A recent study showed that IFN-γ increased Txnip expression in β-cells via inhibition of miR-17, whereas overexpression of miR-17 alleviated the cytokine effect.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%
See 1 more Smart Citation